2016
DOI: 10.1126/science.aad5497
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory evolution of innate immunity through co-option of endogenous retroviruses

Abstract: Endogenous retroviruses (ERVs) are abundant in mammalian genomes and contain sequences modulating transcription. How ERV propagation impacts the evolution of gene regulation remains poorly understood. Here we show that ERVs have shaped the evolution of a transcriptional network underlying the interferon (IFN) response, a major branch of innate immunity. We found that lineage-specific ERVs have dispersed numerous IFN-inducible enhancers independently in diverse mammalian genomes. CRISPR-Cas9 deletion of a subse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

41
878
4
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 814 publications
(972 citation statements)
references
References 48 publications
41
878
4
6
Order By: Relevance
“…AIM2 is a member of the interferon‐inducible PYHIN (PYRIN and HIN domain‐containing) family proteins (also known as p200‐family proteins) and serves as the front line of defense against pathogen infection via caspase‐1 activation (Chuong et al ., 2016; Gray et al ., 2016; Man and Kanneganti, 2015; Rommereim and Subramanian, 2015). Aberration of AIM2 results in a large number of diseases (Choubey, 2016; Man et al ., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…AIM2 is a member of the interferon‐inducible PYHIN (PYRIN and HIN domain‐containing) family proteins (also known as p200‐family proteins) and serves as the front line of defense against pathogen infection via caspase‐1 activation (Chuong et al ., 2016; Gray et al ., 2016; Man and Kanneganti, 2015; Rommereim and Subramanian, 2015). Aberration of AIM2 results in a large number of diseases (Choubey, 2016; Man et al ., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It was recently shown that transposable elements can acquire a regulatory potential during evolution, and thus have an impact on gene expression (e.g., refs. [70][71][72]. On the other hand, vertebrate Hox clusters are largely devoid of transposable elements, unlike their flanking regulatory regions.…”
Section: Discussionmentioning
confidence: 99%
“…В рамках последней все-таки полученный иммунитет не переводит соответствующие инфекции в статус внутренних позитивных ориентиров для прогрессивного развития форм органической жизни. Правда, в последнее время появляются исследования, доказывающие вирусную природу иммунной системы и некоторых частей ДНК [Chuong, 2016;Brouillette, 2016]. 16 В несколько другом контексте эта идея социальной динамики и культурной диффузии через восприятие чужеродного развивалась Г. Зиммелем в его концепции «Чужака» и независимо от последнего А. Щюцем («the Stranger») [Щюц, 2004: 533-549].…”
Section: имитационно-вирусная природа протестного движенияunclassified